Maternal representations about the provision of care to newborns at risk: a collective discourse - Zani, Adriana Valongo (2014)
Aim: To capture maternal representations about the provision of care to newborns with very low birth weight in neonatal hospital units. Method: A qualitative study involving 41 mothers interviewed between November 2011 and July 2012. For analysis, we used the Social Representations framework, following the Collective Subject Discourse (CSD) method. Results: Nine central ideas emerged: fear of the unknown, difficulty in accepting being apart from the baby, difficulty in talking about the baby, real possibility of death, feeling of helplessness with regard to their child’s hospitalization, feeling of guilt for failing to care for the child, the wait for a miracle, feelings of confidence with regard to the team, and the satisfaction that proximity to the newborn brings to the mother. Conclusion: We identified a number of negative aspects such as fear of the unknown separation from the child. On the other hand, the proximity to the newborn was identified as a facilitating aspect. We emphasize the need for intervention aimed at using the mother as a support and the gradual integration of the mother into the care provision process